Tinjauan Sistematis Pengembangan Smart Digital Learning Berbasis Masalah PISA dan Kearifan Lokal dalam Pembelajaran Matematika SMP - Ashari, Nur Wahidin; Suradi, Suradi (Pusat Studi Bahasa dan Publikasi Ilmiah, 2025)
This study is a Systematic Literature Review (SLR) aimed at analyzing the need for developing Smart Digital Learning (SDL) based on PISA-oriented problems and local wisdom to enhance junior high school students’ numeracy literacy. The review covers national and international articles relevant to SDL, mathematical literacy, Problem-Based Learning (PBL), and ethnomathematics. A total of 20635 articles were initially identified from Scopus, ERIC, Google Scholar, and Garuda databases, and through a systematic screening process, 30 studies published between 2020–2025 were selected for in-depth analysis. The reviewed literature covers topics on SDL, mathematical literacy, Problem-Based Learning (PBL), and ethnomathematics. The findings indicate that the use of digital technologies such as games and Augmented Reality effectively improves students’ motivation, problem-solving, and metacognitive abilities. In addition, the integration of PBL and local wisdom contexts strengthens students’ mathematical communication and reasoning skills. However, the literature review also reveals that studies integrating PISA, PBL, and local wisdom within a unified digital learning system remain limited. Therefore, it is necessary to develop a direction for Smart Digital Learning that not only emphasizes technological aspects but also contextualizes mathematics learning through PISA problems and cultural values. The results of this study recommend the design of SDL as an innovative learning solution capable of balancing global standards with local contexts, thereby enhancing students’ numeracy literacy in a meaningful and sustainable manner.